Essays on macroeconomic policy and inflation in lower-income countries - Mumuni, Zakari (2018)
This thesis critically analyses the deficits-inflation nexus and inflation targeting in lower-income countries. Previous research has found a significant relationship between fiscal deficits and inflation in low-income countries, but not in high-income countries. It is shown here that the crucial factor is the quality of institutions. The relationship holds in countries with weak institutions, but not in those with strong institutions, even if their per capita GDP is quite low. The implication is that institutional improvements can enhance macroeconomic outcomes in poor countries. The robustness of the findings is tested using various measures of institutional quality. On the other hand, we provide new insights on inflation targeting (IT) in low-income countries. Previous research on inflation targeting has focused on high-income and emerging market economies since low-income countries (LICs) were slow to adopt the framework. Only recently has enough data accumulated for the performance of IT in LICs to be assessed. We show that unlike in emerging markets, in LICs IT is not been effective in reducing inflation. Weak institutions, a typical feature in LICs, do help explain this especially when we examine their role under floating exchange rate regimes. Finally, we characterise monetary policy in Ghana, one of the earliest low-income countries to adopt an IT framework, but where IT has not been very successful in reducing the levels and volatility of inflation within a modified Taylor rule. We investigate whether poor conduct of monetary policy is responsible for the poor performance of IT and find that is not. Monetary policy reaction functions are similar to those estimated for countries with successful monetary policies, and interest rates respond in the theoretically recommended way to inflation shocks.